(untitled) (Research, Society and Development, 2021)
Introduction: Cardiorespiratory arrest (CPA) is called the absence of heartbeat and apnea. This condition is classified as a serious clinical condition that is increasingly incident in Intensive Care Units, for this reason, health professionals need to be prepared to act in this context. Objective: To analyze cases of cardiac arrest in different care sectors. Methodology: A search was carried out in the Virtual Health Library (VHL) in July 2021. The search for materials that contained in their abstract the descriptors in health sciences (DeCS) was started Nurse; Cardiac arrest; Intensive care unit. The "and" rounding tool was used and the following criteria were adopted for the selection of articles: complete materials, in Portuguese, in article format and with a ten-year time frame (2011-2021). Results: Three articles were analyzed and, based on a thorough reading, the category with the theme "Assignments and challenges encountered by nursing professionals at the time of CPR" was created. Final Considerations: The daily problems experienced by professionals nurses in the assistance to victims of CPA are several and among them, the lack of qualification of workers, the lack of investments in permanent education and the lack of fast, standardized and high-quality support is accentuated. are conditions that pose a high danger of obstacles and even death.